Increasing Mathematics Learning Outcomes Through Zoom Meeting Assisted Problem Based Learning (PBL) Learning Models - Samsudin, Muhammad (Universitas Sebelas Maret, 2022)
This research is motivated by the teacher's difficulties in learning mathematics. The lack of teacher ability in designing and implementing learning models is an obstacle to children's success in the process of learning mathematics. The aim of this research is to improve the learning outcomes of students in grade VI Elementary School by using the Problem Based Learning model assisted by zoom meetings. The research used was Classroom Action Research (CAR) of two cycles which previously carried out the pre-cycle stage of action, each cycle consisting of 4 stages: planning, implementing, observing, reflecting. The results obtained from the implementation of the research showed an increase, namely the average value of the test in the first action was 84 and the average value of the second action test was 94 while in the pre-cycle stage the average value was 72. These results indicate that the Problem Based Learning (PBL) learning model can improve student learning outcomes, especially the Class VI Mathematics at SDN 9 Boyolali.